2005
DOI: 10.1002/dvdy.20557
|View full text |Cite
|
Sign up to set email alerts
|

Monocilia on chicken embryonic endocardium in low shear stress areas

Abstract: During cardiovascular development, fluid shear stress patterns change dramatically due to extensive remodeling. This biomechanical force has been shown to drive gene expression in endothelial cells and, consequently, is considered to play a role in cardiovascular development. The mechanism by which endothelial cells sense shear stress is still unidentified. In this study, we postulate that primary cilia function as fluid shear stress sensors of endothelial cells. Such a function already has been attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 38 publications
5
114
0
3
Order By: Relevance
“…Previously, we have shown a flow-dependent distribution pattern of ciliated EC in the chicken heart and vasculature that coincided with shear stress-related gene expression (Van der Heiden et al, 2006). In the heart, 30 -70% of the endocardial endothelial cells present a cilium in areas of low and oscillatory shear stress, whereas the arterial endothelial cells are devoid of luminal cilia.…”
Section: Chec Retain Cilia In Vitromentioning
confidence: 64%
See 2 more Smart Citations
“…Previously, we have shown a flow-dependent distribution pattern of ciliated EC in the chicken heart and vasculature that coincided with shear stress-related gene expression (Van der Heiden et al, 2006). In the heart, 30 -70% of the endocardial endothelial cells present a cilium in areas of low and oscillatory shear stress, whereas the arterial endothelial cells are devoid of luminal cilia.…”
Section: Chec Retain Cilia In Vitromentioning
confidence: 64%
“…EC have also been described to possess a primary cilium (Collin and Collin, 2004) that was "shed off" by high levels of fluid flow (Iomini et al, 2004). We have shown that embryonic EC of the heart and blood vessels indeed present a primary cilium in a shear stress-dependent fashion (Van der Heiden et al, 2006). In addition, disturbed flow exposed "athero-prone" areas in the adult mouse vasculature, i.e., the carotid sinus, the branch points of the aortic arch, and its inner curvature, show ciliated EC before and after the onset of atherogenesis .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The re-absorption of cilia in the endothelium of the endocardial cushions is in agreement with other studies showing that primary cilia are resorbed in response to sheer stress. 135,[137][138][139] Fluid shear stress is known to play important roles in trabeculation, cardiomyocyte proliferation, and establishment of the conduction system, and changes in the fluid flow leads to CHD. 140 Interestingly, mouse endothelial cells that form stunted primary cilia (e.g derived from the Tg737 orpk mutant) or are mutated in Pkd1 show impaired response to shear stress, 141 and mice with mutations in Kif3a, Lrd, Pkd2, 136 and Ift88/Tg737 21,142 have defects in chamber maturation.…”
Section: Cardiac Primary Cilia In Heart Developmentmentioning
confidence: 99%
“…Primary cilia are found on endocardial cells in the developing chick heart, predominantly on cells in areas of low shear forces (Van der Heiden et al, 2006). This localization is probably due to the active remodeling of the heart that takes place in regions of high shear forces.…”
Section: Heart and Blood Vessel Primary Ciliamentioning
confidence: 99%